Green advertising appeal and consumer purchase intention - Tih, Siohong; Chan, Kuan-Thye; Amin Ansary,; Ali Ahmed, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study investigates the influences of various types of green message (self-benefit and other-benefit appeals) on consumers’ green purchase intentions among Malaysians and Iranians. In particular, this study examines whether the type of appeal affects consumers’ purchase intentions differently, and whether this effect is moderated by the consumer’s home country. A sample of 117postgraduate students was exposed to one of two printed hypothetical green messages promoting either self-benefit or other-benefit appeals. The results reveal that other-benefit appeal influences purchase intentions more than self-benefit appeal. Furthermore, green product purchase intention among Malaysian postgraduate participants is higher as compared to that of the Iranians. However, home country does not moderate the relationship between appeal type and purchase intentions. Both theoretical and practical contributions are discussed.